Theory and methods of the development of participative management of students’ activity in higher educational institutions - Uprugina P. D. (Humanitarian, 2018)
the article is devoted to theory and methods of the development of participative management of students’ activity in higher educational institutions. The author considers the pedagogical principles of development of participative management of the secondary school students’ study and makes conclusions about the future specialists.
Keywords: методика; теория; учебная деятельность студентов; methods; theory; партисипативный стиль управления; participative management; students’ activity in higher educational institutions